The Contemporary Resonances of Classical Pragmatism for Studying Organization and Organizing. Issue 1 (January 2022) - Simpson, Barbara; den Hond, Frank
The legacy of classical American Pragmatism – Peirce, James, Dewey, Addams, Mead, Follett and others – in organization theory is significant, albeit that much of its influence has come through implicit and indirect routes. In light of recent calls for an empirical stance as an alternative to the prevailing metaphysical stance in organizational research, we reread Pragmatism as a process philosophy that can profoundly inform process views of organization and organizing. Our particular reading highlights Pragmatism's emphasis on process and emergence, its theory of knowing as fallible and experimental, its denouncing of dualisms, its future-oriented meliorism, its sensitivity to ethics and democracy, and its positioning of experience as both the start and end of inquiry, arguing that these features lay invaluable groundwork for the study of organization and organizing. We advocate a reappraisal of this legacy, mobilizing seven articles from the back catalogue of this journal in a virtual special issue that demonstrates how classical American Pragmatism can reinvigorate the field while also opening up new questions and new ways of questioning.